Emotion regulation treatment of alcohol use disorders : helping clients manage negative thoughts and feelings /: helping clients manage negative thoughts and feelings. (2018) - Stasiewicz, Paul R; Bradizza, Clara M; Slosman, Kim S
No abstract available